Trachoma and Its Determinants in Mojo and Lume Districts of Ethiopia - Negash Yalew, Kassanahun; Medhanit, Getachew; Mekonnen, Getachew; Jemaneh, Atsbha Asrat (Pan African Medical Journa)
Introduction: Trachoma is a public health problem in Ethiopia accounting for 35?50% of cases of blindness. This study aimed to determine the prevalence of trachoma and its determinant factors in Mojo and Lume districts. Methods: A cross sectional community-based survey was conducted. From the two districts, a total of 23 clusters were selected by a multistage cluster random sampling technique. A total of 731 households were visited using structured questionnaires and clinical manifestation of trachoma was examined by ophthalmic nurses to assess stages of trachoma in children between ages 1 and 9 years and adults aged above 15 years. Results: Among 431 examined children, 54(12.53%) had trachomatous inflammation-follicular (TF) and 43(9.98%) had trachomatous inflammation-intense. Among the adults we found 12 (1.68%) prevalence of trachomatous trichiasis. The presence of latrine (p=0.02), garbage disposal system (p=0.05), main source of water consumption (p=0.01) and keeping animals in the living room were found to be significant risk factors (p<0.001). Conclusion: Prevalence of trachoma was found to be 12% which is higher than the WHO standard. The study also identified that there was significant association between the different stages of trachoma with risk factors such as source of water and keeping animals in the living room.
This article is published as part of the supplement “AMREF´s evidence in advancing the health of women and children” Supplement sponsored by AMREF - African Medical and Research Foundation © Kassahun Negash Yalew et al. The Pan African Medical Journal - ISSN 1937-8688. This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/2.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.
Keywords: Trachoma